Etymologien til ordet ”jordmor” - Jahr, Ernst Håkon (Nordiske Studier i Leksikografi, 2012)
All standard Norwegian dictionaries today give the same etymology of the word jordmor (‘midwife’): “From jord (‘earth’), because in earlier times women gave birth on dirt floors.” This contribution contests this etymology and discusses four different etymologies suggested by various scholars. Special focus is given to a suggestion that jordmor originates from Old Norse jóð (‘foetus, small child’) via *jóðamóðir/*jóðsmóðir > jord(e)mor (with an unetymological r). Another Scandinavian word for midwife, ljosmor/ lysmor, can also be accounted for by this origin: *jóðsmóðir > josmor (with the loss of ð), which was then reinterpreted as ljosmor (‘light mother’).